Marketing Analysis for a Footwear Company– Part 1 (British Journal of Multidisciplinary and Advanced Studies, 2024)
The purpose of this paper was to conduct a marketing analysis of a Footwear Company in Durban, South Africa. Environmental analysis tools such as PEST and SWOT were utilised in order to identify the factors that can impact the performance of this company. Porter’s five forces that shape industry competition and consumer behaviour and decision making was also explored. The significant findings revealed that the Footwear Company is susceptible to threats from larger international brands and its market share is dependent mainly on the population of South Africa. A marketing plan to address these threats will be presented in a future paper.